From al-Andalus to Khurasan : documents from the medieval Muslim world - Sijpesteijn, Petra. (Islamic History and Civilization, 2007)
As in many areas of pre-modern history, the study of medieval Islamic history has been critically hindered by the lack of available evidence. Unlike many parallel fields, however, the shortage of contemporary documentary evidence for medieval Islam has less to do with the survival of documents and archives as with their accessibility. A rich documentary legacy survives, but because of its inaccessibility and unfamiliarity to all but the most specialised scholars in the field, it has remained sadly underutilised. This volume contributes to the redressing of that problem. It collects papers given at the conference "Documents and the History of the Early Islamic Mediterranean World," including editions of unpublished documents and historical studies, which make use of documentary evidence from al-Andalus, Sicily, Egypt, the Arabian Peninsula, Syria and Khurasan. For more titles about Papyrology, please click here .